The Effect of Different Liquid on Temperature Uniformity and Stability in Microbath 7102 - Waslina Rangkuti; Kerista Tarigan; Syahrul Humaidi; Marhaposan Situmorang; Erna Frida; Yahya Darmawan (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
Microbath Fluke Type 7102 is used for thermometer calibration. In the calibration process, Microbath uses liquid media as heat conductor. Liquid media in Microbath during the calibration process there is a value of uniformity and temperature stability. The value of temperature uniformity and stability is an influential component in determining the value of measurement uncertainty (U95). The smaller the U95 value, the better the calibration results. This is a factor in this study to analyse the uniformity and temperature stability of liquid types of Water, Methanol and Glycol. The uniformity test method is carried out using 5 (five) point measurements, where the reference point is in the middle. The stability test method uses the measurement of one reference point. Uniformity and stability values are connected to determine the uncertainty of measurement value using the GUM (Guide to the expression of Uncertainty in Measurement) method. The analysis showed that Methanol is more homogeneous than Glycol and Water, with values of 0.0855 ºC < 0.0942 ºC < 0.1030 ºC. Water is more stable than Methanol and Glycol, with values of 0.0021 ºC < 0.0027 ºC < 0.0028 ºC. The time to stabilise Methanol is better than Water and Glycol. Methanol can be stabilised with ± 35 - 40 minutes, Water needs ± 38 - 40 minutes and Glycol needs ± 48 - 50 minutes. The relationship between uniformity and temperature stability is that the smaller the uniformity and stability values, the smaller the U95 of a calibration result. The U95 value of Methanol 0.11 ºC, Glycol 0.12 ºC and Water is 0.13 ºC.